KAJIAN POLA PERUBAHAN GARIS PANTAI DAN DSTRIBUSI SEDIMEN (STUDI KASUS PERAIRAN PANTAI KENDAL JAWA TENGAH AKIBAT PEMBANGUNAN PELABUHAN) - Sriyana Sriyana (KEAIRAN, 2005)
As an impact of development of Kendal Port, the coast around the port will be disruption. The accretion and erotion will be happened in certain area in coast. Remind in the development of port should have environmental vision so it is felt important to has a study to know the impact in coastline changing. This study is to know how far the changing of Kendal coastline as effect of development Kendal port and pattern of sediment movement. Method was used to know how far the changing of coastline and movement pattern of sediment by using GENESIS SMS (Surface Water Modeling System) version 7.0. The result of running simulation program yielded that change of coastline will be equal to 15 m until 80 m of per year. The pattern of sediment movement in port basin is 0,25 – 0,30 gr/lt and in outer of port basin is 0,40 – 0,50 gr/lt. This trend followed the angle of incoming dominant wave and the current velocity.